Aging Influences the Efficiency of Attentional Maintenance in Verbal Working Memory. (6th June 2018) - Jarjat, Gabriel; Portrat, Sophie; Hot, Pascal
Abstract: Objectives: Numerous studies reported an age-related deficit in verbal working memory (WM). Beyond the well-established general factors of cognitive aging, the alteration of the specific WM maintenance mechanisms may account for this deficit. This paper aims to investigate the hypothesis that WM attentional maintenance is impaired with age. Method: In a WM task adapted to individual short-term memory and processing speed, younger and older participants maintained letters while verbally responding to a concurrent processing task, in order to constrain the use of rehearsal. Critically, the opportunity to use attentional maintenance was manipulated by varying the cognitive load (CL) of the concurrent processing via its nature and pace. Results: Younger participants outperformed older participants and, in both groups, recall performance decreased as the CL increased. Importantly, in line with our predictions, the CL effect was modulated by age. Older adults benefited less from free pauses that allowed participants to engage in attentional maintenance of WM traces. Discussion: Although still effective in normal aging, WM attentional maintenance seems to be altered. It could therefore be a good candidate to account for WM age-related deficits.